Investigation of the Role of Some Selected Virus Species in Abnormality of Calves - Babacan, Sümeyye; Abayli, Hasan; Tonbak, Sükrü; Tümer, Kenan Çağrı; Polat, Eren; İssi, Mustafa (My University, 2023)
Early embryonic death, fetal resorption, fetal mummification/maceration, abortion, and abnormalities are some of the causes of losses in farm animals. In this study, it was aimed to make recommendations to clinician veterinarians by investigating the presence of bovine viral diarrhea virus (BVDV), Schmallenberg virus (SBV), Akabane virus (AKAV), and bovine herpesvirus-1 (BHV-1) viruses in calves with congenital anomalies. A total of 34 calves of different breeds and sexes, between 1 day and 2 months of age which were brought to Fırat University Animal Hospital for diagnosis and treatment and found to have congenital anomalies after a general clinical examination during visits to the neighboring villages, were included in the study. The abnormalities detected in the calves were as follows: Hydrocephalus, cerebellar hypoplasia, brahignati inferior, mandibular laterognathism, arthrogryposis, cheilognathopalatoschisis, coccygeal agenesis, atresia ani, bouleture/arqure, ocular and orbital deformities, dermoid cysts, miniature, renal and urinary system anomalies. PCR results showed pestivirus was detected in 6 of 34 (17.6%) calves with abnormalities. After sequencing, the expected PCR product (288 nucleotides) for pestivirus showed high identity (97% and above) to the BVDV-1 strain/isolates in the GenBank. In conclusion, although the primary purpose of cattle breeding is high meat and milk yield, it is also very important to continue the production process with healthy newborn calves. For this reason, even if congenital anomalies are seen at a low rate in calves, they should not be underestimated as they will cause economic losses, and we believe that clinician veterinarians should not ignore these diseases.
Keywords: Virus; Calf; Congenital anomalies